The Role of Butyric Acid in Treatment Response in Drug-Naïve First Episode Schizophrenia - Li, Xue; Fan, Xiaoduo; Yuan, Xiuxia; Pang, Lijuan; Hu, Shaohua; Wang, Yunpeng; Huang, Xufeng; Song, Xueqin (Frontiers in Psychiatry, 2021)
Background Butyric acid, a major short-chain fatty acid (SCFA), has an important role in the microbiota–gut–brain axis and brain function. This study investigated the role of butyric acid in treatment response in drug- nai ̈ve first episode schizophrenia. Methods The study recruited 56 Chinese Han schizophrenia inpatients with normal body weight and 35 healthy controls. Serum levels of butyric acid were measured using Gas Chromatography-Mass Spectrometer (GC-MS) analysis at baseline (for all participants) and 24 weeks after risperidone treatment (for patients). Clinical symptoms were measured using the Positive and Negative Syndrome Scale (PANSS) for patients at both time points. Results At baseline, there was no significant difference in serum levels of butyric acid between patients and healthy controls (p = 0.206). However, there was a significant increase in serum levels of butyric acid in schizophrenia patients after 24-week risperidone treatment (p = 0.030). The PANSS total and subscale scores were decreased significantly after 24-week risperidone treatment (p’s＜0.001). There were positive associations between baseline serum levels of butyric acid and the reduction ratio of the PANSS total and subscale scores after controlling for age, sex, education, and duration of illness (p’s＜0.05). Further, there was a positive association between the increase in serum levels of butyric acid and the reduction of the PANSS positive symptoms subscale scores (r=0.38, p=0.019) after controlling for potential confounding factors. Conclusions Increased serum levels of butyric acid might be associated with a favorable treatment response in drug-naïve, first episode schizophrenia. The clinical implications of our findings were discussed.